HUMIDITY EFFECT TO 5G PERFORMANCES UNDER PALEMBANG CHANNEL MODEL AT 28 GHZ - Bengawan Alfaresi; Zainudin Nawawi; Reza Firsandaya Malik; Khoirul Anwar; Levy Olivia Nur (SINERGI, 2020)
The telecommunication has a tremendous improvement in terms of data rates and bandwidth requiring sufficient frequency allocation and wideband spectrum availability. The millimeter-wave frequency band is one of the solution to these requirements, however communications in this band is facing new challenges on the climate effect to the channel propagation  In this paper, we propose a 5G channel model considering the effect of humidity based on the characteristic of the natural environment of Palembang city. The channel model is represented by power levels and delay called a Power Delay Profile (PDP and is derived based on a series of computer simulations using parameters of nature in Palembang. The 5G channel model is important to further derive the outage performance to be used as the theoretical performance of 5G in Palembang since the the Shannon Channel Capacity Theorem is involved in the derivation. We conduct a series of computer simulations to evaluate the validity of the proposed channel model and its characteristics. We found that humidity affect to the performances, where high humidity makes the performances of outage and BER slightly worse, although the effect may be ignored for some applications. The results of this paper are expected to be the references for the development and implementation of 5G Networks especially at the mm-Wave band in Palembang.